The effect of organizational communication on knowledge sharing and human resource performance in the Indonesian Islamic Student Community Organization / Rofrofin Khudhriyana BM, Muhammad Rosyihan Hendrawan and Soesilo Zauhar - BM, Rofrofin Khudhriyana; Hendrawan, Muhammad Rosyihan; Zauhar, Soesilo (Faculty of Information Management, 2023)
The entire organization, during this pandemic, is required to be able to maintain its sustainability. In this case, the performance of human resources is very important to encourage organizational performance in achieving its goals. The level of performance of human resources is influenced by the knowledge and skills of individuals. This study aims to describe and analyze the level of organizational communication, knowledge sharing, and human resource performance and examine the effect of organizational communication on human resource performance directly or indirectly through knowledge sharing in The Indonesian Islamic student community organizations such as the Higher Education Commissariat (PKPT) of the Nahdlatul Ulama Student Association (IPNU) – Nahdlatul Ulama Female Student Association (IPPNU) at Brawijaya University (UB) and The Islamic University of Malang (UNISMA). This study uses a quantitative approach with the type of explanatory research, which is used to examine the effect between variables. The results showed that the level of organizational communication, knowledge sharing, and human resource performance in both PKPT IPNU was high. While the results of the hypothesis test show that organizational communication has a significant positive effect on human resource performance (0.011 < 0.05), organizational communication has a significant positive effect on knowledge sharing (0.000 < 0.05), and knowledge sharing has a significant positive effect on human resource performance. (0.002 < 0.05), and organizational communication has a significant positive effect on human resource performance through knowledge sharing (0.000 < 0.05). This study concludes that the implementation of organizational communication in both organizations is good, so the intensity of knowledge sharing is frequent. This ultimately has an impact on the good performance of human resources as well. The Effect of Organizational Communication on Knowledge Sharing and Human Resource Performance in The Indonesian Islamic Student Community Organization